An evaluation of the execution of the educational and informational needs of women during hospital treatment for breast cancer - Karwat, Irena Dorota; Kołłątaj, Witold; Kołłątaj, Barbara; Piecewicz-Szczęsna, Halina (Polish Journal of Public Health, 2010)
Introduction. Breast cancer is the most common type of malignant cancer among women in Poland. The number of new cases increases annually. The aforementioned rise in the number of new breast cancer cases and the fact that the tumour is usually diagnosed relatively late are the main causes behind the large number of patients who require hospital care and aggressive treatment annually. Aim. The aim of the study was the evaluation of informational and educational needs of women undergoing hospital treatment for breast cancer. Material and method. The tested group consisted of 116 women – the members of the Post-Mastectomy Women’s “Amazons” Club in Lublin aged 35-82, who had breast cancer diagnosed within the 1992-2008 period. The examination was retrospective in character. An original questionnaire was applied. The questions concerned the execution of needs in relation to the adjustment and hospitalisation of women treated for breast cancer. Results. The analysis of the answers given in the questionnaire indicates that there are a lot of informative and educational problems which have not been solved for many years, concerning the hospitalization of women with breast cancer. It is noted that 8-18 years ago, no less than ⅓ of polled patients were satisfied with their knowledge on the subjects of: the side effects and the complications after the therapy applied, dietary recommendations for patients treated for cancer, the possibilities for rehabilitation therapy, the safety of applying an alternative therapy as well as coping with stress. The same worries were also relevant 2-7 years ago. Over the years, some new pervading and disquieting questions have appeared – such as the question concerning the new type of medications, prebiotics and probiotics which aid the cancer treatment. More than ½ of polled women enumerated the following sources of necessary information as most valuable: brochures aimed at women with cancer, contacts with oncologists, physiotherapists and psychologists, as well as former breast cancer patients. These opinions had remained almost unchanged for many years. Conclusions. The women suffering from breast cancer constitute a large group of people with specific educational, medical and psychological needs. Currently, many of these needs remain unfulfilled. Some of them may be met by the application of better educational and information procedures.